Central Insulin-like Growth Factor-1 Treatment Enhances Working and Reference Memory by Reducing Neuroinflammation and Amyloid Beta Deposition in a Rat Model of Sporadic Alzheimer’s Disease - Joanna Dunacka; Beata Grembecka; Irena Majkutewicz; Danuta Wrona (Pharmaceuticals)
Background/Objectives: Brain insulin resistance is a potential causal factor for dementia in Alzheimer’s disease (AD). Insulin-like growth factor-1 (IGF-1), a neurotrophin, plays a key role in central insulin signaling and neuroprotection. Intracerebrovenitricular (ICV) administration of streptozotocin (STZ) disrupts insulin signal transduction, leading to brain insulin resistance, which may mimic the early pathophysiological changes in sporadic AD (sAD). In this study, we investigated whether restoring insulin signaling through ICV injection of IGF-1 could ameliorate spatial memory deficits during sAD progression in a rat model induced by ICV STZ injection. Methods: Male Wistar rats (n = 40) were subjected to double ICV injections of STZ (0.75 mg/kg/ventricle, days 2 and 4) and IGF-1 (1 μg/single injection, days 1 and 3), and placed at the Morris water maze (MWM) at baseline, 7, 45 and 90 days after injections. Reference (days 1–3 and day 4 MWM)) and working (days 5–8 MWM) memory, microglia activation (CD68+ cells), and amyloid β (Aβ) deposition (immunohistochemistry) were measured. Results: We found that ICVIGF-1 administration protected working memory demonstrated as (1) reduced latency to reach the platform, and reduced swimming distance in trials 3 (p < 0.05) and 4 (p < 0.01) on days 45 and 90 post-injection and (2) a short-term (up to 45 days post-injection) enhancement of reference memory, manifested by a reduction in swimming distance and latency (p < 0.05). Furthermore, IGF-1 treatment reduced neuroinflammation in CA2 (p < 0.05) and Aβ deposition in CA1(p < 0.01) of the hippocampus. Conclusions: Central IGF-1 attenuates spatial memory deficits in the ICVSTZ-induced sAD model by reducing neuroinflammation and Aβ accumulation in the hippocampus.